ChemInform Abstract: Complex 5d Magnetism in a Novel S = 1/2 Trimer System, the 12L Hexagonal Perovskite Ba4BiIr3O12. Issue 3 (21st January 2014) - Miiller, Wojciech; Dunstan, Matthew T.; Huang, Zixin; Mohamed, Zakiah; Kennedy, Brendan J.; Avdeev, Maxim; Ling, Chris D.
Abstract The title compound is prepared by solid state reaction of BaCO3, Bi2O3 (10% excess), and Ir metal (1173 K, 2 d).